Sinbaglustat ameliorates disease pathology in a murine model of GM1 gangliosidosis without affecting CNS ganglioside levels - Rouven Wannemacher; Lorna Jubran-Rudolf; Isabel Zdora; Eva Leitzen; Karl Rohn; Virginie Sippel; Christoph Paschen; Peter Blattmann; Wolfgang Baumgärtner; Ingo Gerhauser; Michel Alexander Steiner (Neurobiology of Disease)
Sinbaglustat is a brain-penetrating small molecule that inhibits the non-lysosomal glucocerebrosidase (GBA2) and, with lower potency, glucosylceramide synthase (GCS). Sinbaglustat has passed clinical phase I. Our preclinical study assessed its efficacy in a transgenic mouse model of GM1 gangliosidosis, lacking a functional β-galactosidase enzyme (Glb1−/−). Starting at 4 weeks of age, mice were either treated with a nominal dose of 10 or 300 mg/kg/day of sinbaglustat or remained untreated. Wild-type (WT) mice served as control. Body weight, clinical and neurological signs, and motor function was assessed until 17–18 weeks (4 months) and 30 weeks (7 months) of age when mice were euthanized for ex vivo assessments. In comparison to WT, Glb1−/− mice showed the expected accumulation of GM1 gangliosidosis-related sphingolipids, neuropathology, and behavioral deficits. Both dosages of sinbaglustat left GM1 and lyso GM1 levels in the brain unaffected but delayed the onset of motor impairment and progression of clinical disease in Glb1−/− mice with the higher dose being more efficacious. Histologically and immunohistochemically, both treatment groups of Glb1−/− mice displayed reduced neuronal vacuolation. Only the higher dose of sinbaglustat decreased axonal damage and astrogliosis, which was also associated with a decrease of the axonal/neuronal damage marker plasma neurofilament light at 4 months (17–18 weeks). Both doses of sinbaglustat increased the GBA2 substrate glucosylceramide (GluCer) in the brain, while only the high dose reduced GluCer and other glycosphingolipids (GSLs) in the periphery indicating additional inhibition of GCS. We conclude that sinbaglustat had a therapeutic-like effect in the GM1 gangliosidosis mouse model.